Development and Characterization of Novel Interpenetrating Network (IPN) Foams from Epoxy Ester and Aliphatic Epoxy Resin - Kanuprasad Patel; Dhirubhai Desai; Santosh Bhuva (E-Journal of Chemistry)
Diglycidyl ether of bisphenol-A (DGEBA) was reacted with acrylate monomer at variable molar ratios. The reaction between glycerine and epichlorohydrine form glycidyl ether of polyol aliphatic epoxy resin. The resultant resins were characterized duly. Both the resins were mixed at different ratios with constant high shear stirring. The obtained mixture and suitable additives were heated at 150oC for one and half hour. The so called Interpenetrating Network (IPN) transformed into foams. The performance of foams was evaluated by testing for compression in both parallel and perpendicular to rise direction. The tests were carried out at room temperature and at the elevated temperature. The compression properties showed a decreasing trend for increasing amounts of glycerine resin. The density and thermal properties of epoxy foams were also evaluated. The relation between the composition, density and properties of the foam was analyzed.